The effect of increasing retirement age: A perception of employee in Penjara Jelebu, Negeri Sembilan / Nurul Amira Sarwan and Faeznor Afieqah Ishak - Sarwan, Nurul Amira; Ishak, Faeznor Afieqah (Faculty of Administrative Science and Policy Studies, 2013)
Nowadays, a new retirement policy regarding on the retirement age among civil servants has been increased to 60 years old. This research wants to know about the relationship between the effects of increasing retirement age among civil servants when a new retirement age has been implemented. There are three effects of increasing retirement age which are the effect on productivity level, the effect on younger opportunity and the effect on employee life satisfaction. The research has been conduct on the employees of Penjara Jelebu, Negeri Sembilan with the sample size of 108 employees. This research was using the Spearman Rank-Order Correlation in order to know which effects have significant in contributing the positive effects on increasing retirement age. Thus, the result shows that the productivity level and employee self satisfaction has a significant in contributing the effect on increasing retirement age.